Effect of genotype on performance, vitamin and carotenoid deposition, oxidative stability, fatty acid profile and sensory characteristics in cockerels housed on litter and in mobile boxes on pasture - Michaela Englmaierová; Miloš Skřivan; Tomáš Taubner; Věra Skřivanová (Italian Journal of Animal Science)
The study evaluated the effect of housing system and genotype on performance and breast meat quality in 540 cockerels. Three genotypes of cockerels differing in growth intensity (slow-growing ISA Dual, medium-growing Hubbard JA757 and fast-growing Ross 308) and two housing systems (litter and mobile box on pasture) were compared. The significantly lowest feed conversion (p < .001) was recorded for Ross 308 cockerels housed on litter, while ISA Dual cockerels from mobile boxes had a 74% higher conversion ratio. The highest concentrations of lutein (p = .043) and α-tocopherol (p = .024) in breast meat were found in the cockerels from mobile boxes of genotypes ISA Dual and Ross 308, respectively. Meat stored for five days showed the highest oxidative stability of fat (p = .001) in slow- and medium-growing cockerels housed on pasture. The ISA Dual genotype housed both on litter and on pasture and the Hubbard JA757 genotype from mobile boxes had the highest proportion of polyunsaturated fatty acids in the meat (p < .001). The lowest n6/n3 fatty acid ratio (p = .045) and thrombogenic index (p < .001) and the highest hypocholesterolaemic/hypercholesterolaemic index (p < .001) were recorded in slow-growing chickens with access to pasture. The meat of cockerels fattened on litter was considered more fragrant (p = .013), more tender (p < .001), juicier (p < .001) and overall more acceptable (p = .001). It can be concluded that the ISA Dual genotype showed the highest willingness to graze compared to Hubbard JA757 and Ross 308 cockerels and made the best use of the benefits of pasture fattening, which was reflected in the high quality of the meat. The meat of conventionally housed cockerels was sensorially evaluated as better.Highlights The ISA Dual genotype showed the highest willingness to graze, which was reflected in the higher content of health-promoting substances in meat. The more frequent use of slow-growing cockerels for the purpose of fattening will be hindered by lower performance of the cockerels and low level of meat tenderness.